Price competitiveness and variability in Egyptian cotton: effects of sectoral and economywide policies - Bautista, Romeo M.; Gehlhar, Clemen G. (International Food Policy Research Institute, 1995)
This paper examines the role of price incentives in the observed decline in cotton production during the 1980s and in the apparent improvement in recent years. The following determinants (in an accounting sense) of the changes in the relative producer price of cotton during 1980-92 are quantified: (1) changes in the foreign price; (2) changes in the real exchange rate; and (3) changes in nominal protection and the marketing margin. An estimated model of the real exchange rate for Egypt is used to provide a further decomposition of the changes in the relative cotton price that isolates the effect of policy-related factors. The comparative effects of sectoral and economywide policies are analyzed based on three alternative policy regimes in terms of the average price and variability of annual price levels over the period 1971-1992. Government interventions are found to reduce both the long-run price incentive and short-run price variability in Egyptian cotton. Various approaches in dealing with commodity pice instability in the context of a more open trade regime are indicated.